2021
DOI: 10.3390/su13063449
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Household Handling and Consumption Dynamics of Milk in Peri-Urban Informal Markets in Tanzania and Kenya: A Gender Lens

Abstract: Milk, provided it is safe, provides important micronutrients that can combat hidden hunger (undernutrition). Many peri-urban poor people in Tanzania and Kenya use informal markets to purchase milk in order to provide nutritional benefits to their families. Household decision-making processes play an influential role in how much milk to buy and how it is treated. This exploratory qualitative study, conducted in peri-urban Nairobi and Dar es Salaam, examined how access to milk, control over milk handling and saf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 26 publications
(30 reference statements)
1
12
0
Order By: Relevance
“…McNamara and Wood ( 2019 ) also found that age and gender‐differentiated taboos affected the intake of certain foods which are central to the Tajik diet. In terms of decision making, Galiè et al ( 2020 ) also concluded that the woman's limited decision‐making power had significant effect on nutritious diet (milk intake) of the entire family. These findings point to the fact that gender could be an important factor in yam preference and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…McNamara and Wood ( 2019 ) also found that age and gender‐differentiated taboos affected the intake of certain foods which are central to the Tajik diet. In terms of decision making, Galiè et al ( 2020 ) also concluded that the woman's limited decision‐making power had significant effect on nutritious diet (milk intake) of the entire family. These findings point to the fact that gender could be an important factor in yam preference and consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Milk sold in the informal sector-unpasteurized and unpackaged-is an important source of affordable and accessible protein for low-income consumers in Tanzania. It is cheaper relative to packaged milk from the formal sector, is accessible and available in small quantities, and consumers perceive it to be of high quality (Galiè et al, 2021). Our study demonstrates that quality and safety are key factors driving trading decisions throughout the chain in Tanzania's dominant informal milk sector and shows scope for using those as drivers of upgrading the sector.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 74%
“…Among all milk-containing infant food collected, porridge was more likely to contain Bacteroides MST markers than other food types. In Kenya, milk is often added to porridge as part of the diet ( Galiè et al, 2021 ). The milk may not reach a sufficient temperature to kill Bacteroides and other microbes if milk is added after boiling, which would explain BacR detection.…”
Section: Discussionmentioning
confidence: 99%